Human T Cell Lymphotrophic virus infection among sexually active individuals in Nigeria: A cross sectional study - Babatunde Olusola; Adedayo Faneye; Yewande Nejo; Adewale Opayele; Solomon Bakarey (Scientific African, 2019)
Introduction: Human T Cell Lymphotrophic virus (HTLV) is endemic in many regions of the world including Nigeria but not ubiquitous. It has been shown to be causally associated with T cell leukaemia and other myelopathies. Heterosexual contact is the major route of HTLV transmission. STDs patients, pregnant women and other sexually active individuals have been shown to be at risk of HTLV infection. However, there is limited information on population mostly at risk in endemic countries like Nigeria. Here we determined the prevalence of HTLV I and II infection amongst three sexually active populations comprising of pregnant women, adults and teenagers as well as sexually transmitted infections (STI) clinic attendees. Methods: Sera of 463 participants comprising 184 pregnant women, 82 adult, 103 teens and 94 individuals attending STI clinics in Nigeria were tested for HTLV I/II specific antibodies using ELISA technique. Results: Overall, 17 (3.7%) individuals had antibodies to HTLV I/II. The infection was highest among persons attending STI clinics (11.7%) and lowest among pregnant women (0.5%). Reproductive age group (21–50years) was associated with HTLV I/II infection across both gender. STI clinic attendance (Odds ratio: 14.012; P-value = 0.018) and male gender (Odds ratio: 2.828; P-value < 0.05) were strong predictors of HTLV I/II infection. Conclusions: HTLV infection is prevalent among sexually active persons in Nigeria. Individuals with STIs are at a higher risk of HTLV I/II infection. Individuals attending STI clinics should be routinely screened for HTLV infection to aid prevention and control efforts. Keywords: Sexually transmitted infections, HTLV, Heterosexual transmission, Nigeria